2004
DOI: 10.1002/jctb.1029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcination temperature on catalyst reducibility and hydrogenation reactivity in rice husk ash–alumina supported nickel systems

Abstract: Nickel catalysts supported on rice husk ash-alumina (Ni/RHA-Al 2 O 3 ) were prepared by an incipient wetness impregnation method. Characterization included TGA, DSC, TPR, XRD, and BET. Results show that the decomposition of the nickel compound to nickel oxide was complete above 500• C. The TPR analysis revealed a strong interaction between nickel and support, and a decrease in reducibility of NiO with increasing calcination temperature. The XRD analysis of Ni/RHA-Al 2 O 3 catalyst precursors demonstrated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…Furthermore, from Fig. 3 [21]. From the XRD patterns, it can be seen that the phases of the LDH samples can change significantly when the calcination temperature is increased from 600 to 900 C. This confirms the occurrence of phase transformation reactions during high temperature thermal treatments of the LDH material.…”
Section: 3supporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, from Fig. 3 [21]. From the XRD patterns, it can be seen that the phases of the LDH samples can change significantly when the calcination temperature is increased from 600 to 900 C. This confirms the occurrence of phase transformation reactions during high temperature thermal treatments of the LDH material.…”
Section: 3supporting
confidence: 60%
“…1, it can be seen that the decomposition reaction appeared to complete after 600 C in terms of weight loss. Phase transformation of nickel oxide to spinel and formation of solid solution commenced and continued at higher calcination temperatures [21].…”
Section: Textural Characteristics Of the Ldh Derived Ni Catalystmentioning
confidence: 99%
“…The activity of the mesoporous silica-supported catalysts for the FTS was found to be affected by the reducibility of cobalt and iron oxides. This dependence of catalytic activity and selectivity on the reducibility of the metal species was also observed on non-silica supports in other reactions [ 27 , 28 , 29 , 30 , 31 ]. Since the catalyst reducibility is such an important feature of FTS catalysts, one of the aims of this paper is to study the reducibility of differently-prepared Fe-MCM-41 materials.…”
Section: Introductionsupporting
confidence: 74%
“…The symmetry of the main peak (2 nd ) is compatible with that of the corresponding peak in the TPR profile of Fe 2 O 3 and therefore assigned to the Fe 3 O 4 → Fe 0 reduction step. Another notable feature in Figure 16 is the shift of the reduction peaks to higher temperature upon increasing the calcination temperature from 450 °C to 560 °C, a phenomenon that has been attributed to enhanced metal-support interactions [ 28 , 29 , 53 ]. It can be concluded that calcination at 450 °C produces highly dispersed Fe species on 1 o Si-MCM-41 and that higher calcination temperatures induces stronger metal-support interactions which renders the reduction of the Fe species difficult.…”
Section: Resultsmentioning
confidence: 99%
“…The previous investigations [31][32][33][34][35] have shown that for the supported metal catalysts, the preparation conditions have direct influences on the surface properties of the catalyst, the dispersion of surface metal oxides on the support, and the interaction between metal oxides and the support. This implies that the particle sizes of metal Ni, the extents of metal-support interaction, the surface basicity of the catalyst, and the promotion efficiency of Mg promoter on the c-MA-supported Ni-Mg catalysts, which control the catalyst activity and stability and the resistance to coke deposition in the steam reforming of hydrocarbons, can be affected through varying the thermal treatment conditions such as calcination temperature in the preparation process.…”
Section: Introductionmentioning
confidence: 99%